2016
DOI: 10.1534/genetics.116.187419
|View full text |Cite
|
Sign up to set email alerts
|

The Activity-Dependent Regulation of Protein Kinase Stability by the Localization to P-Bodies

Abstract: The eukaryotic cytoplasm contains a variety of ribonucleoprotein (RNP) granules in addition to the better-understood membrane-bound organelles. These granules form in response to specific stress conditions and contain a number of signaling molecules important for the control of cell growth and survival. However, relatively little is known about the mechanisms responsible for, and the ultimate consequences of, this protein localization. Here, we show that the Hrr25/CK1d protein kinase is recruited to cytoplasmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 74 publications
4
30
0
Order By: Relevance
“…This localisation is characteristic of the CK1 family [27]. Although, the origins of these structures are unknown in Leishmania , human CK1δ and HRR25, its Saccharomyces cerevisiae ortholog are known to localise to P-bodies, which protect the kinase from degradation, especially during stress [11, 50]. P-bodies also store repressed mRNAs that mainly encode for regulatory processes [50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This localisation is characteristic of the CK1 family [27]. Although, the origins of these structures are unknown in Leishmania , human CK1δ and HRR25, its Saccharomyces cerevisiae ortholog are known to localise to P-bodies, which protect the kinase from degradation, especially during stress [11, 50]. P-bodies also store repressed mRNAs that mainly encode for regulatory processes [50].…”
Section: Discussionmentioning
confidence: 99%
“…In budding yeast, ScHrr25/CK1δ is localised to the bud neck, where it is essential for proper cytokinesis, and to endocytic sites, where it is required for their initiation and stabilisation [8] [9] [10]. Lastly, ScHrr25/CK1δ is recruited to cytoplasmic processing bodies (P-bodies), which protects the active kinase from the cytoplasmic degradation machinery during stress [11]. These few examples reflect the tight association of CK1 localisation to its functions, suggesting that investigating its localisation may increase our knowledge on this kinase and allow the identification of potential novel functions.…”
Section: Introductionmentioning
confidence: 99%
“…The species distribution of this domain suggests that its main function is to cooperate with Mam1 in a monopolin‐specific role, likely in regulation and/or localization of Hrr25's kinase activity. A recent report has implicated this domain in its localization to P‐bodies, however, suggesting that the domain may also play a role in Hrr25 localization outside the context of monopolin (Zhang et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…These findings have led researchers to propose that these RNP granules could have a role in the rewiring of cellular signaling networks under specific conditions of stress (25,30,31). Work from our laboratory has shown that the Hrr25 protein kinase is efficiently localized to P-bodies under all conditions tested in the yeast Saccharomyces cerevisiae (25,31). Hrr25 is an essential enzyme and is the yeast ortholog of the ␦/ isoforms of the mammalian CK1 protein kinase (32).…”
mentioning
confidence: 99%
“…Hrr25/CK1 enzymes have been shown to have conserved roles in ribosome maturation, vesicle trafficking, DNA repair, clathrin-mediated endocytosis, and meiosis (33)(34)(35)(36)(37)(38)(39)(40)(41)(42). The association with P-body granules is also evolutionarily conserved, as the human CK1␦ enzyme was detected within P-body foci in HeLa cells (31). In yeast, this P-body localization has been shown to be important for the maintenance of the normal cellular levels of Hrr25 by shielding this protein from degradation by the proteasome (31).…”
mentioning
confidence: 99%